Life Is But a Story: Female pleasure and agency in Beyoncé's autobiographical film. (1st September 2020) - Patrick, Stephanie
While the rise of new media has led to a blurring of stars' public personae and private, intimate lives, the musician, in particular, has long been expected to share their private, authentic self through their music. This is certainly the case with superstar Beyoncé, whose 2016 solo album Lemonade was widely received as a revealing portrait of her marriage to hip hop mogul Jay-Z. Yet Beyoncé has long been playing with the public‐private divide as a key part of her star persona. Her decision to limit media interviews has allowed her to maintain unprecedented control of her star image; an image that is now corralled through the texts that she herself circulates via her music, videos and other media. One such notable, yet under-examined text is her 2013 autobiographical film Life Is But a Dream. Both the narrative and the production of the film serve to teach audiences how to read the rest of Beyoncé's cultural work; as work that is fully controlled by her and intended for women. This pedagogical film disrupts common readings of her image and performances as being in the service of a male gaze, thus opening up new pleasures and potentials for female fans more broadly and Black female fans more specifically. Life Is But a Dream is thus a central, rather than a periphery text in Beyoncé's star image, complementing and complicating the work she produces across other media formats.